Anterior segment optical coherence tomographic characterisation of keratic precipitates. Issue 5 (October 2020) - Shipton, Chloe; Hind, Jennifer; Biagi, John; Lyall, Douglas
Highlights: AS-OCT can identify KPs and may assess response to treatment in anterior segment inflammation of uncertain aetiology. Acute and active inflammation generally demonstrated hyperreflective KPs on AS-OCT compared to longstanding inflammation. In the case of infective interface keratitis, no specific changes were identified at the graft-host interface. AS-OCT should not be used to differentiate infective from inflammatory KPs as there were no significant differences. Endothelial pigment deposits were differentiated from KPs with smaller, poorly defined, hyporeflective deposits. Abstract: Background/objectives: Anterior segment optical coherence tomography (AS-OCT) can be used to visualise keratic precipitates (KPs) on the corneal endothelium. However, there has been no correlation between characteristic clinical appearances of KPs and AS-OCT morphology. We wished to assess the potential diagnostic role of AS-OCT in patients presenting with inflammatory eye disease and KPs. Subjects/methods: Six patients with inflammatory KPs were compared to one patient with infective interface keratitis following Descemet Membrane Endothelial Keratoplasty (DMEK) and one patient with endothelial pigment. AS-OCT was performed in each case and morphological features of the KPs were compared. Reflectivity of KPs was also compared numerically by measuring their relative lightness. Results: AS-OCT images in acute and active inflammation generally demonstrated hyperreflective KP variants in comparison to conditions with moderate or longstanding inflammation. In the patient with infective interface keratitis, KPs were evident on the endothelial surface but no changes could be identified at the graft-host interface. There were no significant differences between infective and inflammatory KPs to help distinguish between the two. Endothelial pigment deposits were clearly differentiated from keratic precipitates with smaller, poorly defined deposits on the endothelium surface which were isoreflective to the cornea. Conclusion: Hyperreflective KPs could be suggestive of newly deposited KPs and active inflammation; they may also be increased in KPs of herpetic origin. AS-OCT should not be used to differentiate infective infiltrate from inflammatory KPs if a patient were to present with post-operative inflammation and interface infection should still be suspected even if only endothelial deposits are identified on AS-OCT. AS-OCT may be used as a diagnostic and monitoring tool to assess response to treatment in cases where anterior segment inflammation of uncertain aetiology is present.